Merajut Komunikasi Antar Budaya di Indonesia - Sayogo, Budi (Merajut Komunikasi Antar Budaya di Indonesia, 2011)
Indonesia is a nation-state that have hererogeneous pattern in various aspects. this condition is potential for friction,conflict,and communicational gep between ethnic/tribal to heppen. To minimize the accurrence of inter-ethnic conflice , a bond of communication between cultures that is equal and convergent is needed. With an interactive cross curtural communication, therefore confrontation between ethnic/tribal can be minimized, social tensions can be prevented, and the integrity of the Unitary Republic of Indonesia can be maintained.